Pengaruh Komitmen Organisasi terhadap Kesiapan Berubah pada Karyawan Geoff Max Footwear.co di Kota Bandung - Fazzari, Faishal Ali; Juwitaningrum, Ita; Wulandari, Anastasia (Program Studi Psikologi Universitas Pendidikan Indonesia, 2021)
The global pandemic, caused by the coronavirus and now commonly referred to as Covid-19, emerged towards the end of 2019. This unprecedented pandemic has wreaked havoc on nearly all companies across the globe, leaving no industry untouched. The ability of individuals to adapt to change has proven to be a pivotal factor in the success of organizations undergoing transformation. Among the crucial determinants of one's preparedness for change lies organizational commitment. This research endeavors to examine the profound influence of organizational commitment on the readiness for change among employees at Geoff Max Footwear.co, situated in the city of Bandung. Employing a quantitative approach, the study was analyzed by regression. incorporated a sample size of 140 participants. The outcomes of this investigation illuminate the multifaceted impact of organizational commitment, comprising three distinct dimensions: affective commitment, continuance commitment, and normative commitment. All dimensions demonstrated a noteworthy level of significance, with p-values of 0.000. This compellingly indicates that organizational commitment significantly affects the preparedness for change within the organization. Pandemi global terjadi pada akhir tahun 2019 yang disebabkan oleh virus corona atau sekarang biasa disebut dengan Covid-19. Pandemi ini menyebabkan hambatan hampir seluruh perusahaan di dunia. Kesiapan individu untuk berubah merupakan faktor yang penting dalam keberhasilan organisasi untuk melakukan perubahan. Salah satu faktor yang memainkan peran penting terhadap kesiapan untuk berubah yaitu komitmen organisasi. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh komitmen organisasi terhadap kesiapan untuk berubah pada karyawan Geoff Max Footwear.co di Kota Bandung. Penelitian ini dianalisis dengan analisis regresi ganda. Hasil penelitian ini menunjukkan adanya pengaruh komitmen organisasi yang terdiri dari tiga dimensi yaitu komitmen afektif, komitmen berkelanjutan, dan komitmen normatif. Setiap dimensi menunjukkan hasil signifikansi yang berarti adanya pengaruh komitmen organisasi terhadap kesiapan untuk berubah.